Studies in risk perception and financial literacy: applications using subjective belief elicitation - Schneider, Mark (School of Economics, 2019)
The concept of literacy has grown from “reading literacy” to now encompass many different domain-specific topics and skill sets, such as health literacy, financial literacy, and computer literacy. The way literacy is talked about, examined, measured, and communicated has also evolved. Literacy measures began as a simple metric of counting the number of individuals in a country that could read and dividing that count by the total population to compute the percentage of literate individuals. However, this approach ignores situations in which an illiterate person has access to a literate person that could read to them. This was the premise of research in development economics that introduced the measure of effective literacy, which accounts for potential positive externalities that could arise from access to a literate individual. This dissertation expands on the idea of effective literacy and introduces a concept of extended literacy, which applies to a decision-maker having access to an external scaffold during the decision-making process. The scaffolds considered include access to the internet, to an anonymous person as part of a group, and to a household member. The research presented here measures extended financial literacy under these various scaffolds. Financial literacy reflects an individual’s knowledge about financial matters, including the management of risks. The research assesses subjects’ knowledge about interest and inflation, budgeting, and longevity risk. The techniques used to measure literacy reflect state-of-the-art advances in subjective belief elicitation that allow for the recovery of each decisionmaker’s entire underlying subjective distribution. This method generates a rich characterization of subjects’ beliefs and allows the construction of various measures of literacy, welfare, bias, and confidence with respect to a known, true answer. Using controlled laboratory and artefactual field experiments with real rewards and incentivized elicitation of beliefs, we find that these scaffolds reliably enhance literacy. We relate the notion of extended literacy to concepts in economics, cognitive science and philosophy, such as effective literacy, embedded literacy and embodied literacy.